Effect of Financial Performance and Firm Size on Dividend Policy (Empirical Study on Consumer Goods Sector Issuers 2017-2020) - Bella Tamara; Bambang Mulyana (Ridwan Institute, 2022)
This study aims to examine and analyze the effect of Profitability (ROE), Liquidity (CR), Leverage (DER), and Firm Size (SIZE) on Dividend Policy (DPR) either partially or simultaneously. This research uses causal associative research. The population in this study is all issuers of the Consumer Goods sector listed on the Indonesia Stock Exchange with an observation period of 2017-2020 of 63 issuers. The sample used purposive sampling method, then 14 issuers were obtained as samples. The analytical method used in this study is panel data. The results showed that partially ROE has a significant negative effect on the DPR, CR has an significant positive effect on the DPR, DER has an insignificant positive effect on the DPR, and SIZE has an insignificant positive effect on the DPR. Simultaneously ROE, CR, DER, and SIZE have a significant effect on DPR. The coefficient of determination in this study is 49.45%.